A CONTEXTUAL ANALYSIS OF ARTICLE 16 OF THE IRELAND–NORTHERN IRELAND PROTOCOL. Issue 3 (July 2022) - Melo Araujo, Billy
Abstract: Article 16 of the Ireland–Northern Ireland Protocol annexed to the EU–UK Withdrawal Agreement is an escape clause which allows the parties to deviate from their obligations under certain conditions. This article maps out the main features of the safeguards provision in the Protocol in light of international trade law and international relations literature on treaty design. It provides a detailed examination of the safeguards provision in the Protocol and highlights the key design flaws associated with this regime as well as some potential solutions to such flaws.